Machine learning-based solution reveals cuproptosis features in inflammatory bowel disease - Liu, Le; Liang, Liping; Yang, Chenghai; Chen, Ye (Frontiers in Immunology, 2023)
Background: Cuproptosis-related genes (CRGs) have not yet been studied for their clinical significance in IBD. Methods: We screened CRGs that had a signiﬁcant correlation with immune status, which was determined utilizing ImmuneScore and GEO (GSE75214). Furthermore, utilizing the R package ‘CensusClusterPlus’, these CRGs’ expression was used to obtain different patient clusters. Subsequently, GSEA, CIBERSORT, and ssGSEA assessed the variations in the enrichment of gene function and the abundance of immune cell infiltration and immune functions across these clusters. Furthermore, WGCNA and analysis of DEGs were executed, and for the purpose of identifying hub genes between these clusters, the construction of PPI network was done. Lastly, we validated the immune proﬁles associated with the expression of CRG using the GSE36807 and GSE10616 datasets. Results:Three CRGs, PDHA1, DLD, and FDX1, had a signiﬁcant association with different immune profiles in IBD. Patients were subsequently classified into two clusters: low expression levels of DLD and PDHA1, and high expression levels of FDX1 were observed in Cluster 1 compared to Cluster 2. According to GSEA, Cluster 1 had a close association with the RNA processes and protein synthesis whereas Cluster 2 was substantially linked to environmental stress response and metabolism regulations. Furthermore, Cluster 2 had more immune cell types, which were characterized by abundant memory B cells, CD4+ T memory activated cells, and follicular helper T cells, and higher levels of immune-related molecules(CD44, CD276,CTLA4 and ICOS) than Cluster 1. During the analysis, the PPI network was divided into three significant MCODEs using the Molecular Complex Detection (MCODE) algorithm. The three MCODEs containing four genes respectively were linked to mitochondrial metabolism, cell development, ion and amino acid transport. Finally, external validation cohorts validated these findings, and scRNA-seq profiling demonstrated diverse intestinal cellular compositions with a wide variation in CRGs expression in the gut of IBD patients. Conclusions: Cuproptosis has been implicated in IBD, with PDHA1, DLD, and FDX1 having the potential as immune biomarkers and therapeutic targets. These results offer a better understanding of the development of precise, dependable diagnosis and treatment of IBD.